Neglect of Plasmodium vivax malaria. - Baird, J (2007)
Plasmodium vivax infects 130-435 million of the 2.6 billion people living at risk of infection. Recent studies suggest that vivax malaria can become lethal in a similar way to severe falciparum malaria. First-line therapies remain unchanged after 50 years. Despite evidence of failing chloroquine efficacy, little work has assessed the problem or explored alternative therapies. Primaquine treatment, the only therapeutic option against relapse, might also be failing. No licensed primary chemoprophylactic agent protects travelers from relapse. Misdiagnosis of species now affects clinical decisions resulting in inadequate therapy for P. falciparum and P. vivax. All of these factors demonstrate the lack of research on P. vivax.